Molecular basis of autosomal dominant neurohypophyseal diabetes insipidus. Cellular toxicity caused by the accumulation of mutant vasopressin precursors within the endoplasmic reticulum. - M Ito; J L Jameson; M Ito (The Journal of Clinical Investigation, 1997)
Mutations in the arginine vasopressin (AVP) gene cause autosomal dominant familial neurohypophyseal diabetes insipidus (FNDI). The dominant inheritance pattern has been postulated to reflect neuronal toxicity of the mutant proteins, but the mechanism for such cytotoxicity is unknown. In this study, wild-type or several different mutant AVP genes were stably expressed in neuro2A neuroblastoma cells. When cells were treated with valproic acid to induce neuronal differentiation, each of the mutants caused reduced viability. Metabolic labeling revealed diminished intracellular trafficking of mutant AVP precursors and confirmed inefficient secretion of immunoreactive AVP. Immunofluorescence studies demonstrated marked accumulation of mutant AVP precursors within the endoplasmic reticulum. These studies suggest that the cellular toxicity in FNDI may be caused by the intracellular accumulation of mutant precursor proteins.